Estudo do processo de gramaticalização do verbo DANAR para marcação de aspectos no português brasileiro - Thaís Franco de Paula (2014)
This essay aims to show a diachronic study of the grammaticalization process of the verb DANAR from the Brazilian Portuguese. We sustain that this verb is passing through a linguistic innovation process, integrating the construction V1DANAR + (pron) + (prep) + V2infinitive towards a marking of the the inceptive aspect that cumulates with the process of making the action longer (durative aspect) in events such as: Ele danou a falar, Eu danei a chorar. Wed like to describe the recategorization of the verb DANAR, which has been semantically disregarding until assuming a grammatical function, that is why we carried out a search in the linguistic grammaticalization / variation. In order to do so we draw on a data base Corpus do Português, which has offered us some occurrences of DANAR, in the Brazilian Portuguese, in the centuries XIX and XX. Through the hypothesis that DANAR has been becoming more grammaticalizated in the XXI century and with the verification that its integrated construction is more typical in informal oral contexts, we used the social network Twitter as a data source, once we have found on it a written register of informal context. We have verified the grammaticalization of DANAR based on semantic, syntactic and frequency criterion. We have also submitted the data under Hopper (1991) principles. The obtained results confirm that DANAR is actually passing through a grammaticalization process.